Hormones and overtraining - Duclos, M. (First international symposium sciences and practices in swimming, 2006)
The diagnosis of overtraining remains a clinical diagnosis. Hormone dosages can be carried out at rest or after an exercise of maximal or sub-maximal intensity. At rest, the Hormone dosages have a limited value for the biological diagnosis of overtraining because of the great inter-individual variability in hormone concentrations. Thus, it is necessary to know the values of the hormones for the subject at rest and in good physical condition in order to Interpret future results. A standardized lest has yet to be defined during exercise. In conclusion, even if certain paths become apparent with regards to a relation between hormones and overtraining, it remains too early to confirm a diagnosis of overtraining on the basis of hormone dosages.